SIKAP DAN KEPUASAN KONSUMEN DALAM PEMBELIAN BOLEN PISANG CV MAYANG SARI DI KOTA BANDAR LAMPUNG - Reza Dwi Meisanto; Rabiatul Adawiyah; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to determine attitudes, purchasing patterns and customer satisfaction on banana bolen CV Mayang Sari. This research method uses a survey method. Samples of this study consisted of 40 consumers who had purchased and / or consumed banana bolen 3 times. The data analysis methods used were descriptive, Fishbein's Multi-attribute model, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The attributes used in this study are price, taste, flavor variants, size, texture, product packaging, and accessibility). The results showed that consumers liked banana bolen or had a good attitude with an Ao value of 132.52, the pattern of buying banana bolen CV Mayang Sari by 52.50 percent consumers, namely two boxes (20 pieces) of banana bolen in one transaction with the flavor variant that consumers are most interested in is chocolate 55 percent. The frequency of consumer purchases is 90 percent made once a month, customer Satisfaction Index (CSI) in consuming banana bolen CV Mayang Sari is in the very satisfied criteria, which is equal to 83.82 percent. Based on Importance Performance Analysis (IPA), there is one attribute that falls into quadrant I (Main Priority), namely the taste attribute. In quadrant II (Maintain Achievement) there is one attribute, namely the price attribute, while in quadrant III (Low Priority) there are attributes of size and ease of obtaining products, and in quadrant IV (Excessive) there are several attributes, namely texture, flavor variants, and product packaging.Key words: attitude, banana bolen, CSI, IPA